2010
DOI: 10.1186/1471-2180-10-222
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrological conditions on the Escherichia coli population structure in the water of a creek on a rural watershed

Abstract: Background: Escherichia coli is a commensal bacterium of the gastro-intestinal tract of human and vertebrate animals, although the aquatic environment could be a secondary habitat. The aim of this study was to investigate the effect of hydrological conditions on the structure of the E. coli population in the water of a creek on a small rural watershed in France composed of pasture and with human occupation. Results: It became apparent, after studying the distribution in the four main E. coli phylo-groups (A, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
37
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 41 publications
(47 reference statements)
7
37
1
Order By: Relevance
“…In this study, there was no apparent variation of E. coli groups. The results in this study contrasted with Ratajczak et al (2010) that reported temporal change in phylogenetic groups. Short-term sampling also showed that E. coli groups did not vary significantly and their distribution was similar to monthly samplings (Fig.…”
Section: Phylogenetic Grouping Of E Coli Environmental Isolatescontrasting
confidence: 57%
See 1 more Smart Citation
“…In this study, there was no apparent variation of E. coli groups. The results in this study contrasted with Ratajczak et al (2010) that reported temporal change in phylogenetic groups. Short-term sampling also showed that E. coli groups did not vary significantly and their distribution was similar to monthly samplings (Fig.…”
Section: Phylogenetic Grouping Of E Coli Environmental Isolatescontrasting
confidence: 57%
“…As coastal waters are dynamic ecosystems, both long-term (monthly) and short-term (daily) samplings were carried out to detect for any temporal variation as hydrological processes can change E. coli population structure (Ratajczak et al 2010). A simple and rapid triplex PCR method was used to detect the different phylogenetic groups of E. coli (Clermont et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although the distribution of the commensal E. coli phylogroups depends on the diet or the climate, strains belonging to phylogroups A and B1 are highly adapted to humans and vertebrate animals, the A phylogroup strains being predominant in humans and the B1 strains in animals (10)(11)(12). Interestingly, some strains from the B1 phylogroup persist in water environments (13,14). Furthermore, Escherichia clade strains seem to be rarely isolated in humans (7) and to be environmentally adapted (9).…”
mentioning
confidence: 99%
“…The anthropogenic pressure exerted on the watershed, as well as the stream order of the river, influences not only the level of contamination of surface water but also the diversity of the E. coli population, as previously described by the rep-PCR DNA fingerprinting of E. coli isolated from water from tropical or Canadian watersheds (17,25). The most probable hypothesis is that, once released into water, the environmental conditions exert selective pressure on the E. coli populations originating from human and animal microbiota (primary habitat), involving the loss of part of the population in the secondary habitat and the persistence of other E. coli strains with an adaptive advantage in the environment (8,13,14,26). Thus, the structure of an E. coli population in water reflected both the origin and pathway of fecal bacteria, combined with the survival characteristics of each strain.…”
mentioning
confidence: 99%
“…Because of its simplicity and rapidity, it has been widely used with different purposes, including ecological niche differentiation, propensity to cause diseases and fecal source tracking Escobar-Paramo et al 2006;Johnson et al 2004;Orsi et al , 2008Ratajczak et al 2010; Walk et al 2007). It is based on triplex PCR, and uses the combination of two genes (chuA, the outermembrane hemin receptor gene, and yjaA, which encodes an uncharacterized protein) and a DNA fragment that has been recently identified as part of a putative lipase esterase gene (Tenallion et al …”
Section: Introductionmentioning
confidence: 99%